(3MGTjI Ydi TQM GdJLQjOs - (3GdTjQGRj, eMeO Hf EHQGgje Hf eMeO Hf ESMGb, J (B903 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3KO cfJ cJHJ ChdG Ydi GdTQM GdLOjO ddJLQjO eG SfM dj aj CKfGA GdeWGdYI ChGf GdeHGMKI hGdefGXQI Ke dGM dj Gfg bO jbY dHYV GLdI GdfGS ajg GTJHGg hGdJHGS jMQa Gdcde Yf ehGVYgG (B...s
(3BNQgG (B:s
.. (3aEPG cGf GdehVhY ehLhOG CUdG de jUOb GdehLHI GdaYdjI hEPG cGf ehLhOG hde jcf eJMOG eY GdeMehd aehVhY Jdc GdbVGjG Ef cGf ehLhOG Ch eJMOG (B...s
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\301s
(3cTa GdXfhf (B2\1104s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds